Kepemimpinan Visioner Kiai dalam Mengimplementasikan Visi di Pondok Pesantren - Zuhri Zuhri (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2018)
Educational process services are integration of educational processes and outcomes standards. Educational institutions apply service standards based on the future design of the institution as an organization, namely the Vision. Educational institutions have a vision and organizational goals as guides in achieving their goals, so are Islamic boarding schools. This research is motivated by a phenomenon that is contrary to the strength of the vision of the Islamic boarding school in creating educational processes and services that meet the standards of consumer needs. The performance of the pesantren leadership, namely Kiai, greatly determines the vision that becomes the movement for pesantren organizations to provide excellent educational services. The effectiveness of the organization in Islamic boarding schools is very dependent on the work of the Kiai as a guide, a mover for institutional change, communicator, and mentor. The presentation in this report uses formation; Preliminary, Research Methods, Discussion, and Closing.